Regulation of Two Aspartokinases in Bacillus subtilis - Hampton, Michael L. (1971)
When grown on minimal glucose medium, transformable Bacillus subtilis strains contained two distinct aspartokinases (ATP:l-aspartate 4-phosphotransferase, EC 2.7.2.4). One of these enzymes was inhibited by l-lysine (Lys), whereas the other was insensitive to inhibition but was activated by l-leucine. None of the other amino acids tested had any effect, and the addition of l-threonine did not enhance the inhibition by Lys, in contrast to the concerted inhibition observed for other bacilli. At the end of exponential growth, the Lys-sensitive aspartokinase activity decreased, whereas the Lys-insensitive activity remained relatively constant throughout the stationary phase. The two activities were separated by (NH(4))(2)SO(4) fractionation and Sephadex G-200 chromatography. Growth in the presence of Lys reduced the specific activity of aspartokinase by about 50% and eliminated the inhibition by Lys. In extracts of these cells, only Lys-insensitive activity was found upon (NH(4))(2)SO(4) fractionation and Sephadex G-200 chromatography. Lys apparently repressed the synthesis of the Lys-sensitive enzyme.